Characterization of Schizosaccharomyces pombe ER -Mannosidase: A Reevaluation of the Role of the Enzyme on ER-associated Degradation - Movsichoff, Federico (2005)
It has been postulated that creation of Man8GlcNAc2 isomer B (M8B) by endoplasmic reticulum (ER) alpha-mannosidase I constitutes a signal for driving irreparably misfolded glycoproteins to proteasomal degradation. Contrary to a previous report, we were able to detect in vivo (but not in vitro) an extremely feeble ER alpha-mannosidase activity in Schizosaccharomyces pombe. The enzyme yielded M8B on degradation of Man9GlcNAc2 and was inhibited by kifunensin. Live S. pombe cells showed an extremely limited capacity to demannosylate Man9GlcNAc2 present in misfolded glycoproteins even after a long residence in the ER. In addition, no preferential degradation of M8B-bearing species was detected. Nevertheless, disruption of the alpha-mannosidase encoding gene almost totally prevented degradation of a misfolded glycoprotein. This and other conflicting reports may be best explained by assuming that the role of ER mannosidase on glycoprotein degradation is independent of its enzymatic activity. The enzyme, behaving as a lectin binding polymannose glycans of varied structures, would belong together with its enzymatically inactive homologue Htm1p/Mnl1p/EDEM, to a transport chain responsible for delivering irreparably misfolded glycoproteins to proteasomes. Kifunensin and 1-deoxymannojirimycin, being mannose homologues, would behave as inhibitors of the ER mannosidase or/and Htm1p/Mnl1p/EDEM putative lectin properties.